Caregiver Perceptions of Child Development : A Cross-Sectional Study - Chung, Esther O.; Fernald, Lia C.H.; Galasso, Emanuela; Ratsifandrihamanana, Lisy; Weber, Ann (World Bank, Washington, DC, 2019)
Parents play a crucial role in the promotion of early childhood development, and understanding parental perceptions of early childhood development may help enhance parental investments early in life. To explore this question, caregivers were asked to rank their child's intelligence in comparison with other children in the community, and the rankings were compared with children's scores on an assessment of developmental abilities across multiple domains. Using cross-sectional data on children ages 16-42 months in rural Madagascar, this paper documents the discordance between caregivers' perceived early childhood development with an interviewer-based measure of early childhood development. The paper examines the determinants of caregivers' under- and over-estimation of child development using multinomial logistic regressions. The study finds that caregiver perceptions of early childhood development in Madagascar do not align consistently with an interviewer-based measure. Approximately 8 percent of the caregivers under-estimated and almost 50 percent over-estimated their children's abilities. Better child nutritional status, caregivers with a greater belief in their influence on child intelligence, and higher socioeconomic status were associated with lower odds of under- or over-estimation of early childhood development. Further research is needed to understand the common cues that caregivers use to identify child development milestones, to inform the design of parenting interventions.